2015
DOI: 10.1186/s13054-015-1137-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intracranial pressure monitoring: systematic review and meta-analysis

Abstract: IntroductionIntracranial pressure (ICP) measurement is used to tailor interventions and to assist in formulating the prognosis for traumatic brain injury patients. Accurate data are therefore essential. The aim of this study was to verify the accuracy of ICP monitoring systems on the basis of a literature review.MethodsA PubMed search was conducted from 1982 to 2014, plus additional references from the selected papers. Accuracy was defined as the degree of correspondence between the pressure read by the cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 35 publications
4
34
1
8
Order By: Relevance
“…A recent meta-analysis comparing the accuracy of invasive ICP monitoring approaches showed a pooled mean difference between paired readings of 2 invasive probes of 1.5 mm Hg (95% CI 0.7-2.3 mm Hg). 22 In those studies included in the meta-analysis with 10 or more subjects, the reported SDEs ranged from 1.1 mm Hg to 7.8 mm Hg. Our model-based nICP estimation produced a bias of about 1.0 mm Hg and associated SDE of 5.1 mm Hg, which matches the clinically accepted accuracy and range of precision errors for routinely used invasive ICP monitors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis comparing the accuracy of invasive ICP monitoring approaches showed a pooled mean difference between paired readings of 2 invasive probes of 1.5 mm Hg (95% CI 0.7-2.3 mm Hg). 22 In those studies included in the meta-analysis with 10 or more subjects, the reported SDEs ranged from 1.1 mm Hg to 7.8 mm Hg. Our model-based nICP estimation produced a bias of about 1.0 mm Hg and associated SDE of 5.1 mm Hg, which matches the clinically accepted accuracy and range of precision errors for routinely used invasive ICP monitors.…”
Section: Discussionmentioning
confidence: 99%
“…Many kinds of nontelemetric sensors have been used for ICP measurements, but their use for long-term monitoring is controversial because of the risk of infection through an intracranial-extracranial device and zero drift, as reported in several articles. 1,16 Also, most intraparenchymal sensors cannot be re-zeroed while recording.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence does demonstrate that both IPM pressure monitoring and EVD pressure monitoring have advantages and disadvantages. Drift or zero loss (zero drift) has been discussed primarily for IPM; however, the most recent summary of the literature supports that mean drift is less than 1 mmHg [22]. Similarly, recent articles find that measurement techniques and anatomical reference points are not standardized and may contribute to measurement variability [16,17,23].…”
Section: Discussionmentioning
confidence: 99%